1971
DOI: 10.1159/000162321
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adrenergic Blocking Agents on Passive Cutaneous Anaphylaxis Reactions in the Rat

Abstract: The effects of adrenergic blocking agents on inflammation have been investigated in rats utilising passive cutaneous anaphylaxis induced with anti-BSA antibodies (rat IgGa or rabbit IgG) and BSA. It was concluded that blocking agents do not affect the pathways leading to the release of phlogistic mediators. Our findings have confirmed the role of catecholamines as factors controlling the inflammatory response and have suggested, furthermore, that hormonal activity is mediated by β-adrenergic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Secondly, while there is less evidence to link catecholamines with the type of non-chronic infectious diseases reported in this study, anti-inflammatory properties of catecholamines have been described [35,36]. Qualliotine [37,38] reported that catecholamines reduced the bactericidal activity of leukocytes, and Ignarro and Colombo [39] have shown that catecholamines and cyclic-AMP inhibit the osmotic release of /3-glucuronidase from leukocyte lysosomes.…”
Section: Resultsmentioning
confidence: 73%
“…Secondly, while there is less evidence to link catecholamines with the type of non-chronic infectious diseases reported in this study, anti-inflammatory properties of catecholamines have been described [35,36]. Qualliotine [37,38] reported that catecholamines reduced the bactericidal activity of leukocytes, and Ignarro and Colombo [39] have shown that catecholamines and cyclic-AMP inhibit the osmotic release of /3-glucuronidase from leukocyte lysosomes.…”
Section: Resultsmentioning
confidence: 73%
“…BOL and methysergide both were found ineffective against heterologous hyperim mune antibody-mediated PCA by Levy [10] and us, respectively. /J-adrenergic sympathomimetic agents have been reported to be active against both reagin-mediated PCA [1,5,13] and against hyperimmune antibody-mediated PCA [3,22], Our comparatively more detailed data suggest that individual /J-sympathomimetic drugs may have different effi cacies and dose-response slopes against reagin and hyperimmune antibody-metiated PCA systems. If these observations can be confirmed by extending the dose and time parameters beyond those used in these experi ments, then it might indicate possible involvement of additional selective inhibitory mechanisms, besides stimulation of adenyl cyclase which is a commonly accepted mechanism of inhibition of anaphylactic reactions by /J-adrenergic sympathomimetic drugs [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory action of certain catecholamines in various animal models of acute (14,15) and chronic inflammation (16,17) has been reported. In fact, catecholamines have been thought to play a regulatory role in the inflammatory process (18).…”
Section: (From the Departments Of Pharmacology And Biochemistry Tulamentioning
confidence: 99%